Cultural Resistance to Premarital Health Screening among Prospective Brides and Grooms in Kintamani Bangli, Bali - Dalem, Dewa Nyoman; Anom Kumbara, A. A. Ngurah; Renawati, Pande Wayan; Muhidin , Salut (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
In 2021, the Indonesian government launched a national stunting strategy outlined in Presidential Regulation No.72. As part of this initiative, a program promoting premarital health screening for prospective brides and grooms was introduced through ELSIMIL (Elektronik Siap Nikah dan Hamil), Marriage and Pregnancy Readiness App. Despite being linked to marriage registration and targeting all couples, participation remains low in certain regions, such as Kintamani-Bali, due to cultural resistance. This study explores the underlying causes of the phenomenon using qualitative approaches (observation, in-depth interviews, and document analysis) guided by Foucault's power-knowledge theory and Bourdieu's generative structuralism. Findings reveal that cultural resistance stems from the local bridal seclusion “pingit” tradition, which prohibits brides from publicly announcing wedding plans, and from beliefs that view illness/health conditions within a couple as a private matter, not a shared social concern. The study highlights the need for culturally sensitive strategies to improve the program's acceptance and effectiveness at the community level.